Analysis of Bronchoscopic Findings in Patients Diagnosed with Malignancies - Gaikwad, Dr Deepali R (International Journal of Innovative Research in Medical Science, 2018)
Objective: To evaluate bronchoscopic findigs in patients referred for bronchoscopy. Method: This is a prospective study done at tertiary care centre. Observations of bronchoscopy were noted in patients referred from various departments for flexible fiberoptic bronchoscopy. Results: Of 48 cases studied, 23 cases (47.9%) were males and 25 cases (52.08%) were females. Male to female sex ratio in the entire group was 1: 1.08. The minimum – maximum age range was 21.0 years – 72.0 years and the mean ± SD of age of the entire group was 55.4 ± 10 years. Of 48 cases studied, 32 cases (66.6%) had cancer of esophagus, 13 cases (27.0%) had cancer of lung, 1 case (2.08%) had cancer of ovary, 1 case (2.08%) had cancer of thyroid, and 1 case (2.08%) had cancer of pyriform fossa diagnosis. Of 48 cases of malignancy studied (n=48), 35 cases (72.91%) had normal Bronchoscopic findings and 13 cases (27.08%) had abnormal Bronchoscopic findings. In nonpulmonary malignancies abnormal bronchoscopic findings are 14.28% (n=35) Conclusion: All patients diagnosed of non-pulmonary malignancies should be evaluated for Pulmonary and endobronchial metastases. 2. All patients diagnosed of esophageal malignancy should be evaluated for tracheobroncheal involvement.